'[B]orn at sea, buried at Tarsus, /And found at sea again:' Pericles and Liminal Form. (April 2013) - Hall, Mark Webster
Abstract : In Shakespeare's Pericles, hazard-prone dramatic subjects undergo any number of reductive transformations as they drift towards redemption. Arguing that the logic of these transformations resonates with certain anthropological structures, the paper examines the rituality of this late romance through the lens of liminality. Sequences of both trauma and healing in the play are suggestively compared with the movement of liminal subjects from separation, through trial, to communal reaggregation. Focusing on the patterns of performative language disclosed in Pericles, the author makes the case, moreover, that the choric and repetitive discourses that prompt recuperation in subjects boast liminal qualities themselves, and that our understanding of how the play works to broker its romance subjectivities is made less precarious when we take this into account.